Γ‐Aminobutyric acid receptor alpha 1 subunit loss of function causes genetic generalized epilepsy by impairing inhibitory network neurodevelopment. (15th October 2018) - Samarut, Éric; Swaminathan, Amrutha; Riché, Raphaëlle; Liao, Meijiang; Hassan‐Abdi, Rahma; Renault, Solène; Allard, Marc; Dufour, Liselotte; Cossette, Patrick; Soussi‐Yanicostas, Nadia; Drapeau, Pierre
Summary: Objective: In humans, mutations of the γ‐aminobutyric acid receptor subunit 1 ( GABRA1 ) cause either mild or severe generalized epilepsy. Although these epilepsy‐causing mutations have been shown to disrupt the receptor activity in vitro, their in vivo consequences on brain development and activity are not known. Here, we aim at unraveling the epileptogenesis mechanisms of GABRA1 loss of function. Methods: We generated a gabra1 −/− zebrafish mutant line displaying highly penetrant epileptic seizures. We sought to identify the underlying molecular mechanisms through unbiased whole transcriptomic assay of gabra1 −/− larval brains. Results: Interestingly, mutant fish show fully penetrant seizures at juvenile stages that accurately mimic tonic–clonic generalized seizures observed in patients. Moreover, highly penetrant seizures can be induced by light stimulation, thus providing us with the first zebrafish model in which evident epileptic seizures can be induced by nonchemical agents. Our transcriptomic assay identified misregulated genes in several pathways essential for correct brain development. More specifically, we show that the early development of the brain inhibitory network is specifically affected. Although the number of GABAergic neurons is not altered, we observed a drastic reduction in the number of inhibitory synapses and a decreased complexity of the GABAergic network. This is consistent with the disruption in expression of many genes involved in axon guidance and synapse formation. Significance: Together with the role of GABA in neurodevelopment, our data identify a novel aspect of epileptogenesis, suggesting that the substratum of GABRA1‐deficiency epilepsy is a consequence of early brain neurodevelopmental defects, in particular at the level of inhibitory network wiring.